2019
DOI: 10.1177/1049909119876606
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Team-Based Approach to Improve Communication With Surrogates of Patients With Chronic Critical Illness

Abstract: Background: Clinicians need to deliver prognostic information to surrogates of nondecisional, critically ill patients so that surrogates can make informed medical decisions that reflect the patient’s values. Our objective was to implement a new approach for communicating with surrogates of patients with chronic critical illness. Methods: Surrogate decision makers of patients who were difficult to liberate from mechanical ventilation were prospectively enrolled. Surrogates met with different members of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…30,88,89 Prognostic discussions with adolescent patients are often avoided by clinicians because of a multitude of barriers, including perceived parental preference to not discuss prognosis with their child and worry of limiting hope or optimism. 90 Few interventions to improve prognostic understanding have been tested for pediatric patients 91 ; however, evidence for their use in adult patients and surrogates suggests they may show promise if adapted for pediatric patients. 45,92,93 Communication guides and training may also be useful.…”
Section: Advance Care Planning: Communication Prognostic Awareness An...mentioning
confidence: 99%
“…30,88,89 Prognostic discussions with adolescent patients are often avoided by clinicians because of a multitude of barriers, including perceived parental preference to not discuss prognosis with their child and worry of limiting hope or optimism. 90 Few interventions to improve prognostic understanding have been tested for pediatric patients 91 ; however, evidence for their use in adult patients and surrogates suggests they may show promise if adapted for pediatric patients. 45,92,93 Communication guides and training may also be useful.…”
Section: Advance Care Planning: Communication Prognostic Awareness An...mentioning
confidence: 99%
“…Greenberg et al 28 designed a communication session where families met with providers from each clinical discipline to receive education and patient updates related to the provider's respective domain of care. The clinical providers assumed the role of communication liaison in addition to their typical role on the ICU team.…”
Section: Scheduled Meetings and Liaison Rolementioning
confidence: 99%
“…Previous studies have shown that good communication with the medical team is a predictor of healthcare satisfaction, and that patient satisfaction with healthcare is a predictor of medical treatment adherence. 6,7 However, many factors, such as time constraints or cultural barriers, impair physicians' ability to address questions…”
mentioning
confidence: 99%